(untitled) (Journal of Information Technologies in Education (ITE), 2010)
In this article methodical and technological principles of communication process in distance learning, which are the important constituents of the effective distance course, are analyzed. Communication facilities for the conducting communication process in distance learning are examined. Recommendations for teachers (tutors) for organization of successful and effective learning process with the use of modern communication technologies are pointed.